Pengaruh Konseling Kelompok Regulasi Diri terhadap Peningkatan Regulasi Diri pada Penderita Pembelian Komplusif - Dinda Dwarawati (JIP (Jurnal Intervensi Psikologi), 2015)
The purpose of this research is to understand the effect of self-regulation group counseling for subjects with Compulsive Buying Disorder. The research method was Quasi-experimental, One-group pretest-posttest design. Analysis technique used is descriptive statistics. Subjects consist of three, with the criteria are students in college, women, have compulsive buying disorder, and in medium category for self-regulation. The results of this research after 5 group-counseling sessions are: the counselee 1 (AP) and counselee 3 (MM) show that they get self-regulation increased scores, but the criteria still exist in the medium category. Counselee 2 (ABF) show that her self-regulation increased scores, with increased category of the category of medium to high category. Key words: self-regulation, compulsive buying, group-counseling.